DeFi and Vietnamese Commercial Bank Stocks - Nguyen Mau Ba, Dang; Nguyen Khanh, An; Ngo Thai, Hung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study aims to identify the price spillover effects between decentralized finance (DeFi) and the stocks of Vietnamese commercial banks using a quantile spillover index model (τ) during the period 2018–2025. The results indicate that the connectedness between DeFi and commercial bank stocks is insignificant under stable market conditions (τ = 0.50), but becomes stronger during bearish (τ = 0.05) and bullish (τ = 0.95) market conditions. Notably, DeFi acts as a recipient of shock spillovers from commercial bank stocks across all three market conditions. Furthermore, the time-varying spillover analysis reveals that the connection between DeFi and commercial bank stocks intensifies during periods of high financial market volatility. These findings serve as an important source of information for investors and policymakers amid the ongoing digital transformation of Vietnam’s banking sector.